Eduardo Fernandez’s Contributions to Time Optimization in Classical Guitar Learning - Romero Vizcarra, Daniel Hugo (2017)
The present research proposes a solution to the lack of time in classical guitar learning by analyzing the contributions of Uruguayan musician and teacher Eduardo Fernandez as found in his book Technique, Mechanism, Learning: An Investigation into Becoming a Guitarist. This research presents specific steps so as to apply the cited book to different pedagogical aspects such as musical analysis, fingering, and solutions to technical difficulties.